THE INFLUENCE OF USING INSTAGRAM ON CYBERBULLYING BEHAVIOR IN ADOLESCENTS AT SMK NEGERI 18 JAKARTA SCHOOL - Nugroho, M. Aulia Adi; M. Sopyan (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
With the increasing popularity of social media platforms like Instagram, it is crucial to understand the relationship between platform usage and cyberbullying behavior in order to promote a safe online environment for adolescents. This study aims to investigate the impact of using Instagram online media on cyberbullying behavior among teenagers at SMK 18 Jakarta. A quantitative approach is employed, utilizing a correlational method to examine the relationship between at least two factors. The study population consists of all students attending SMKN 18 Jakarta in grades 10, 11, and 12 in 2020, with a total of 210 students. The sample size of 100 students is determined using purposive sampling techniques. Data collection techniques include questionnaire deployment, field observation, interviews, and literature review. Validity and reliability testing are conducted using the Person Product moment correlation technique, and the data are analyzed using SPSS version 23. The study findings reveal that Instagram usage significantly influences cyberbullying behavior. The coefficient of determination analysis reveals that the Instagram variable explains 53.8% of the variance in cyberbullying behavior, while the remaining 46.2% can be attributed to other factors not examined in this study. This research highlights the need to address cyberbullying on Instagram and promote responsible social media usage among teenagers. Strategies should be developed to increase awareness of the impact of cyberbullying and foster empathy among users. Educational initiatives and support systems can help mitigate the negative effects of cyberbullying and create a safer online environment for adolescents.